Epidemiological characteristics and trends of notified enteric fevers in Germany, 2001 to 2023 - Christina Frank (Eurosurveillance)
Background Enteric fevers (EF) are caused by infections with Salmonella Typhi (STY) or Salmonella Paratyphi (SP) A-C (except the SPB enteric pathovar) and exhibit increasing antimicrobial resistance (AMR). Notification is mandatory in Germany. Aim To describe characteristics and trends of notified EF cases in Germany. Methods We analysed German EF notifications 2001–2023 fulfilling the case definition. We calculated numbers of imported EF cases per 100,000 air travellers by country of exposure 2012–2023. Results In 2001–2023, 2,670 confirmed EF cases were notified: 56% (1,498/2,670) STY, 44% (1,172/2,670) SP, with seasonal peaks in April–May and August–September. Aside from years with COVID-19-related travel restrictions, STY notifications were stable, while SP notifications decreased. Median age of EF cases was 26 years (range: 0–93) and 55% (1,458/2,663) were male. Of cases with information, 93% (2,491/2,670) had fever, 71% (1,906/2,670) diarrhoea, 78% (2,033/2,607) were hospitalised (STY: 85% (1,234/1,459) vs SP: 70% (799/1,148), p < 0.001) and four died (two STY, one SPA, one SPB). Of STY cases, 7% (88/1,221) reported vaccination. Overall, 86% (2,251/2,613) of cases acquired EF abroad, most commonly in India, Pakistan and Türkiye. Ciprofloxacin resistance was reported for 50/59 STY and 16/18 SPA cases and cefotaxime resistance for 10/57 STY cases (exposure: Pakistan (9/10), India (1/10)) with information since 2017. We also report outbreaks and incidence among travellers. Conclusions Most cases were imported and had high hospitalisation rates and AMR. Typhoid vaccination was underutilised, highlighting that additional ways to reach at-risk travellers with information and vaccination offers are needed.